The Contributor in InnerSource - Tigges, Johannes; Drost-Fromm, Isabel (O'Reilly Media, Inc., 2020)
In much the same way that the open source paradigm of software development has become a standard model for building applications using code that's generated and evolved by developers from around the globe, InnerSource development is rapidly becoming the preferred methodology for building software products intended for use only within an organization. InnerSource applies the same principles that have made open source so successful, like code reuse and unleashing the combined talent and expertise of many developers to help build higher-quality solutions faster and more flexibly. Within the InnerSource framework, the Contributor role is one of the most central roles-to put it succinctly, without Contributors, there wouldn't be anything to receive or discuss. In this video course, you learn that there's far more to being a Contributor than simply dumping code in a branch or issue. You'll explore what it takes to become a Contributor in an InnerSource community, including adopting the mindset, habits, technical approaches, and other details of this role. You'll learn about the mechanics of being a Contributor-the nuts and bolts of developing solutions in this unique environment. You'll also examine the Contributor ethos, including the guest-in-home analogy, the indispensable set of principles to which a Contributor needs to adhere to successfully interact in an InnerSource development environment and contribute to the host teams work, foster good relationships, and be a happy InnerSource Contributor. What you'll learn-and how you can apply it What an InnerSource Contributor is and why the role is important How to become an InnerSource Contributor and adopt the mindsets and habits that lead to becoming one Understand the Contributor ethos and mindset of an InnerSource Contributor The mechanics and technical aspects of contribution to ensure success The benefits of being a Contributor: what's in it for me (the guest), the receiving team (the host), and our company? This video is for you because ... You're a possible future Contributor to an InnerSource project and want to know what to expect You're a host team member looking to open your environment to outside contributors via InnerSourcing and you want to know what the expectations and benefits are of the Contributor role You're a product owner looking to support your TC or a (line) manager and want to know how the InnerSource approach is meant to work Prerequisites: We recommend that you first watch t ...